2005
DOI: 10.1089/tmj.2005.11.36
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Diagnosis, Treatment, and Clinical Improvement Among Patients Receiving Telemedicine Consultations

Abstract: The aim of this study was to determine whether outpatient telemedicine specialty consultations to primary care clinicians result in changes in a patient's diagnosis, treatment management, and clinical outcomes. Medical records of patients who received two or more clinical telemedicine consultations in dermatology, psychiatry, and endocrinology were evaluated in a nonconcurrent retrospective analysis. Three indicators were used to measure changes in the processes of care and clinical outcomes: change in diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 29 publications
4
33
1
3
Order By: Relevance
“…17,18 They are lower than the published concordance values obtained when comparing diagnoses between office dermatologists and teledermatologists (64%-88%) as specialists would be expected to make similar diagnoses more frequently than nonspecialists compared with specialists (the situation in this study). [19][20][21][22][23] The use of nonspecific terms such as ''rash'' or ''dermatitis'' as provisional diagnoses by the referring nondermatologist providers was frequently applied across a spectrum of nosologically unrelated skin diseases including insect bites, folliculitis, molluscum, and nevi.…”
Section: Discussioncontrasting
confidence: 74%
“…17,18 They are lower than the published concordance values obtained when comparing diagnoses between office dermatologists and teledermatologists (64%-88%) as specialists would be expected to make similar diagnoses more frequently than nonspecialists compared with specialists (the situation in this study). [19][20][21][22][23] The use of nonspecific terms such as ''rash'' or ''dermatitis'' as provisional diagnoses by the referring nondermatologist providers was frequently applied across a spectrum of nosologically unrelated skin diseases including insect bites, folliculitis, molluscum, and nevi.…”
Section: Discussioncontrasting
confidence: 74%
“…3 In 2002, CHT researchers reported improved quality from outpatient telemedicine specialty consultations to primary care clinicians. 4 This study also found that telemedicine consultations resulted in changes in diagnosis and treatment regimens as well as improvement in clinical outcomes, 4 demonstrating that telemedicine has the potential to increase the quality of healthcare in local communities. …”
Section: Analytical and Empirical Informationmentioning
confidence: 84%
“…Review and cardiology and has consistently led to strong patient, caregiver, and provider satisfaction (21,24,(45)(46)(47)(48). Telemedicine has also successfully reduced the costs of healthcare and time related to physician travel in addition to reducing the time and out of pocket expenses for patients and families who may need to travel from remote or hard-to-reach locations for their care (49)(50)(51).…”
Section: More Efficient Use Of Tertiary Care Resourcesmentioning
confidence: 99%